Adoption of information technology for counterproductive behaviour index profiling through polygraphic method - Yusoff, Hashim (2013)
The objective of this research is to design and develop a framework for adoption of information technology for counterproductive behaviour index profiling through polygraphic method. Although the potential for technology use is vast, researchers and practitioners know surprisingly little about the array of technologies being used in organizations or the extent to which these technologies are being used to recruit, screen and select employees. Selecting the right people with high integrity, good qualification and with appropriate competency is fundamental to the success of any organization. Various methods have been utilized in pre-employment, promotion, positioning and posting to ensure the best candidate is selected. In these methods, tools ranging from pencil and papers to polygraph testing have been used to detect counterproductive behaviour. Polygraph instrument collect physiological data from three systems of the human body: respiratory, sweat gland, and cardiovascular activity. In the polygraph test a candidate is subjected to a series of questions to determine his integrity. A certified polygraph examiner will formulate questions asked and familiarize the examinee with the testing procedure. To conduct the polygraph test, the most widely used techniques is the one advocated by the American Polygraph Association (APA). The accuracy of the test is dependent to whether the examiner is qualified, examinee fit for testing, the types of equipment used and whether it is calibration, the types of validated questions asked, environment, the processing of the results. However currently there is no published framework to profile counterproductive behaviour using polygraph. This prompted a research question: What framework can be utilized for adoption of information technology for counterproductive behaviour index profiling using polygraph method? Phased Development Research methodology was used. Four life cycles were conducted to produce the final version (4th Version). The framework was evaluated and improved through the life cycles development and acceptance test through 34 presentations; 28 presentations of papers and participation in exhibitions, workshops, seminars, conferences locally and six presentations at international level. Three awards were received at international level. Ten major counterproductive behaviours were identified and covered namely alcohol use, computer abuse, credibility, customer service, fundamental data, illegal drug use, sexual harassment, theft propensity, work attitude, and work history. Three metaphors areas of concerns: little or no concerns for lower scorers (Angel), normal concerns for medium scorers (Human) and serious concerns for higher scores (Devil) were developed with the ability of producing radar charts for each areas of concern. The method comprises of four phases namely: Phase One - Pre Polygraph Phase utilizing multiple perspective approach for question formulation and polygraph testing preparation; Phase Two - Polygraph Testing Phase; Phase Three – Index Profiling Phase; and Phase Four – Historical Profile Management Phase. Major contributions of this research are the framework developed and web-based information system named POLYDETECTTM and can be served through www.polydetect.com.my.